PELATIHAN MANAJEMEN USAHA DAN PEMBUATAN MERK - Aprih Santoso; Witjaksono E.H; Emaya Kurniawati (Universitas Islam Indonesia, 2020)
The purpose of this PKM is to provide training on business management and counseling on the importance of a brand for the production so that the product is more widely known to the market. The main problem of partners is ignorance about how to do a good business starting from planning, implementation to marketing and also not knowing the importance of a brand for a product. The solution offered is the provision of training on business management, the legality mechanism of business licenses. The output of the activity to be achieved so that partners can develop the business accompanied by adequate legality of establishment, so that business operations can take place according to existing provisions, the results of the training can support the business success of business actors in the Genuksari Village and have been successfully implemented. This was proven by the enthusiasm of the trainees to follow and discuss (including the question and answer process) routinely.